Peran Bank Syariah dalam Mengimplementasikan Inklusi Keuangan Syariah di Kecamatan Sakra Timur Kabupten Lombok Timur NTB - Imam Hidayatullah; M Irwan; Titiek Herwanti (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2019)
This study aims to study how the role of Islamic Banks in implementing Financial Inclusion in Sakra Timur District, East Lombok Regency, West Nusa Tenggara Province. This study uses descriptive qualitative with a predetermined sample (Purposive) then Snowball is done to the next sample. The results of this study are Islamic Banks have an important role in increasing the inclusion (access level) of Islamic finance for the surrounding community which is discussed by the community that uses Islamic Bank Institutions of 84.62%, while those using 15.38%. The banks used are BTPN Syariah, NTB Syariah Bank, Bank Rakyat Indonesia Syariah (BRI Syariah). The level of Islamic Financial Inclusion which is enhanced by the role of the government in making policies, such as that carried out by the NTB Provincial Government that converted NTB Bank to NTB Syariah Bank, this policy increases the level of users of Islamic Financial Institutions increasing.